Survival of malarial acute kidney injury in children: A prospective analytical study - Panda, Prakash Chandra; Mishra, Nihar Ranjan; Bhoi, Samira; Rout, Sradhananda; Soren, Girtha; Poddar, Chandrakant (Indian Journal of Child Health, 2019)
Introduction: The renal involvement has been reported in Plasmodium falciparum, Plasmodium malariae, and recently in Plasmodium vivax infection. Although malaria is highly endemic in the rural locality of Odisha and a significant proportion of severe malaria causes acute renal complication, there is no definite study on the survival of malarial acute kidney injury (AKI) in children of the setup of the current study. Objective: The objective of the study was to find out the survival of malarial AKI in children. Methods: A prospective analytical study was conducted from October 2016 to September 2018 in the postgraduate department of pediatrics, of a tertiary care hospital in Odisha, after approval from the Institutional Ethics Committee. Children with smear-positive and/or quantitative buffy coat (QBC) positive malaria were included in the study. All the relevant data (age, gender, duration of hospital stays, stages of AKI, signs, and symptoms of AKI, serum urea and creatinine, electrolytes, and routine hemogram) were collected, validated and results were analyzed in terms of one-way ANOVA and Kaplan–Meier survival analysis. Results: Out of 202 malarial cases, 50.4% (102) cases were found to be suffering from malarial AKI. Out of 102 malarial AKI children, 68% were affected due to falciparum infection, 12% due to vivax, and rest 20% due to mixed infection. The median duration of survival in days between three stages of AKI was significant as evidenced by Tarone-Ware Chi-square=48.365 (df=2), p=0.000. Conclusion: Mortality was 6% and all of these deaths belong to Stage 3 AKI; furthermore, the morbidities are more in Stage 3 as compared to other stages.